2021
DOI: 10.1016/j.aohep.2021.100553
|View full text |Cite
|
Sign up to set email alerts
|

Liver function as a predictor of mortality in COVID-19: A retrospective study

Abstract: Introduction and Objectives In many studies, varying degrees of liver damage have been reported in more than half of the COVID-19 patients. The aim of this study is to determine the effect of liver biochemical parameters abnormality on mortality in critical COVID-19 patients who have been followed in the ICU since the beginning of the pandemic process. Materials and Methods In this study 533 critical patients who admitted to the ICU due to COVID-19 were included. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
(71 reference statements)
2
13
1
Order By: Relevance
“…In our study, higher ALT levels were associated with mortality. Other studies have also found that ALT can predict increased mortality [30,31]. Despite the higher ALT levels in the metformin group, a lower mortality rate may support the protective effect of metformin in our study.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In our study, higher ALT levels were associated with mortality. Other studies have also found that ALT can predict increased mortality [30,31]. Despite the higher ALT levels in the metformin group, a lower mortality rate may support the protective effect of metformin in our study.…”
Section: Discussionsupporting
confidence: 67%
“…After PSM, 120 MF( +) and 120 MF( −) patients were matched. ALT values (median(IQR)) of the MF ( +) group were higher than those of the MF (-) group (25(16-42) vs 19 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), p = 0.003). ICU admission rates, in-hospital mortality rates, and postdischarge mortality rates were higher in the MF( −) group, though not significant.…”
Section: Analysis Of Data After Psm (Matched)mentioning
confidence: 88%
“…In addition, as reported by Salik et al [ 19 ], the COVID-19 patients with liver dysfunction present elevated LDH, CK, ferritin, CRP, and procalcitonin levels compared to patients without liver damage. These elevated parameters levels have been associated with poor prognosis and a high mortality rate.…”
Section: Discussionsupporting
confidence: 61%
“…Elevated liver enzymes have been documented in 15-58% of patients with COVID-19 infection [ 24 ]. Some of the studies including patients without NAFLD have positively correlated elevated transaminases with the severity of COVID-19 illness [ 25 , 26 ]. However, similar to ours, the study by Wang et al (included patients with NAFLD) and Madan et al didn’t find a significant correlation between elevated transaminases and severe events or mortality [ 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%